Employment and Employability Skills of Graduate School Graduates in Tagudin Campus - Dela Cruz, Jonathan L.; Dela Cruz, Tessie L. (Future Science / FSH-PH Publications, 2023)
Graduates' employability is vital in assessing higher education institutions’ performance. The results of tracer studies serve as a basis to identify graduates’ needs to succeed in the workforce. This undertaking aimed to determine graduate school graduates' employment and employability characteristics in a state higher education institution in the Philippines. Specifically, it determined the profile of graduates, employment status, employability characteristics, the extent of contribution and applicability of the skills gained, assessed the graduate program offerings, and recommendations to improve the services of the Graduate School. The study used a descriptive research design. The study gathered data from graduates of the two program offerings of the Graduate School. The questionnaire was used to gather the necessary data and analysed using descriptive statistics such as frequency count and percentage and mean. Based on the results, the graduates have the necessary eligibilities, are employed in public schools, occupy permanent positions, and present employment relevant to the degree earned. In addition, there is high employability of graduates and a high application of the skills gained in graduate school. There is high satisfaction among graduates with the offering and services of the institution. With these conclusions, it is recommended that the existing curriculum shall be reviewed, the improvement of facilities and learning resources, and strong partnership with linkages may be strengthened to sustain the relevance and responsiveness of the existing graduate programs and curriculum.